2004
DOI: 10.1016/j.str.2004.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Specificity, Catalysis, and Regulation of Human Uridine-Cytidine Kinase

Abstract: Uridine-cytidine kinase (UCK) catalyzes the phosphorylation of uridine and cytidine and activates pharmacological ribonucleoside analogs. Here we present the crystal structures of human UCK alone and in complexes with a substrate, cytidine, a feedback inhibitor, CTP or UTP, and with phosphorylation products, CMP and ADP, respectively. Free UCK takes an alpha/beta mononucleotide binding fold and exists as a homotetramer with 222 symmetry. Upon inhibitor binding, one loop region was loosened, causing the UCK tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 44 publications
4
83
0
Order By: Relevance
“…On the other hand, UCK-1 was not able to phosphorylate PSI-6130 or 2Ј-C-Me-C. These UCK-1 results are consistent with the findings of previous structural and biochemical studies, which showed that UCK has a high specificity for the 2Ј-hydroxyl group (28,29). Clearly, the presence of the 2Ј-methyl group also influences the affinities of these nucleosides analogs for UCK.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, UCK-1 was not able to phosphorylate PSI-6130 or 2Ј-C-Me-C. These UCK-1 results are consistent with the findings of previous structural and biochemical studies, which showed that UCK has a high specificity for the 2Ј-hydroxyl group (28,29). Clearly, the presence of the 2Ј-methyl group also influences the affinities of these nucleosides analogs for UCK.…”
Section: Discussionsupporting
confidence: 90%
“…The first of these, choline kinase (CK), phosphorylates choline, to form phosphocholine. Uridine is phosphorylated by uridine-cytidine kinase (CDK) to form uridine triphosphate (UTP) [17], which is transformed in brain to cytidine triphosphate (CTP) by the enzyme CTP synthetase [18]. DHA is acylated by fatty acyl-CoA synthetase [19].…”
Section: Introductionmentioning
confidence: 99%
“…All of these enzymes have high Km's for their substrates relative to normal plasma and brain levels [18]. Uridine conversion to UTP and CTP is enhanced in PC12 cells [24] and rodent brain [14] when the saturation of uridine-cytidine kinase (UCK) [25,26,27,28,29,30] has been increased by pyrimidine administration [17]. Also, the concentration of CTP in brain is insufficient to saturate CTP: phosphocholine cytidylyltransferase (CT) [3,32].…”
Section: Introductionmentioning
confidence: 99%
“…Brain PtdCho synthesis can be enhanced by its three circulating precursors (Kennedy and Weiss, 1956): choline, a pyrimidine nucleoside like uridine or cytidine, and a polyunsaturated fatty acid (PUFA) like docosahexaenoic acid (DHA) (Araki and Wurtman, 1998;Rapoport, 2001;Marszalek and Lodish, 2005); all three readily cross the blood-brain barrier (Li et al, 2001;Spector, 2001). Brain uridine can be phosphorylated by uridine kinase (Suzuki et al, 2004) to form uridine-5′-triphosphate (UTP), which can be aminated (by CTP synthetase) to cytidine-5′-triphosphate (CTP) (Genchev and Mandel, 1974). CTP subsequently forms cytidine-5′-diphosphocholine (CDP-choline) -PtdCho's immediate precursor -which combines with diacylglycerol (DAG) molecules, including those containing PUFA, to produce PtdCho (Weiss, 1995).…”
Section: Introductionmentioning
confidence: 99%